Sistem Informasi Monitoring Inventory IT Aset (SIMONAS)Berbasis Web Pada PT. Metrocom Global Solusi Jakarta - Suparni, Suparni; Hadiyansyah, Hadiyansyah (Politeknik Ganesha Medan, 2018)
PT . Metrocom Global Solutions as a trading company engaged in the provision of information technology devices and services, still has no effective means of doing the processing and reporting of IT assets. IT device management in an enterprise is one important thing to do because the device is one of the company's assets. Monitoring Information System IT Aset Inventory WEB-Based at PT. Metrocom Global Solusi Jakarta consisting of several privileges that admin permissions and manager. With the creation of new systems are supported by the database system expected to overcome the constraints that exist in the management of IT assets at PT . Metrocom Global Solutions Jakarta